Risk taking in social settings: Group and peer effects - Spiros Bougheas; Jeroen Nieboer; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2013)
We investigate experimentally the effect of consultation (unincentivized advice) on choices under risk in an incentivized investment task. We compare these choices to two benchmark treatments: one with isolated individual choices, and a second with group choice after communication. Our benchmarking treatments replicate earlier findings that groups take more risk than individuals in the investment task . In our consultation treatments we find evidence of peer effects: there is significant correlation of decisions within the peer group. However, average risk taking is not significantly different from the benchmark treatment with isolated individual choices. This latter result underlines the importance of payoff-commonality for bringing about higher risk-taking in groups.
Keywords: C91; C92; D71; D80; 330; experimental economics; choice under risk; advice; social influence; peer effects